Cognitive deterioration associated with an expedition in an extreme desert environment. Issue 6 (23rd May 2006) - Maruff, P; Snyder, P; McStephen, M; Collie, A; Darby, D
Abstract : Background: Prolonged exposure to extreme environments may result in cognitive changes that may influence decision making ability and increasing risk of injury or death. Objective: To measure the cognitive performance of a healthy man as he completed a 17 day desert expedition. Method: A computer based cognitive test battery, subjective cognitive rating scale, and measures of physical characteristics were used. Objective cognitive performance was compared with the performance of eight age matched men who remained in their own homes. Results: The speed of psychomotor, attentional, and executive functions decreased as the expedition progressed, but the accuracy of performance remained unaffected. Although some impairments were large, they resolved completely once the expedition was completed. Subjective ratings indicated that the subject had insight into his failing cognitive performance during the expedition. Conclusions: Cognitive performance can be measured repeatedly throughout an expedition in an extreme environment. Cognitive impairment may occur.